2011
DOI: 10.1007/s11431-011-4614-7
|View full text |Cite
|
Sign up to set email alerts
|

Ecological hydrograph based on Schizothorax chongi habitat conservation in the dewatered river channel between Jinping cascaded dams

Abstract: Hydropower development changes the river hydrological regime, thereby altering river ecosystem significantly. One important measure for reducing degradation of ecosystem is to determine ecological flow and implement it by reservoir operation. This paper described a method to calculate river ecological flow based on fish habitat conservation and applied it to Jinping River Bend of Yalong River. Schizothorax chongi was selected as target species, and the fish habitat model coupling with water environmental model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Flow is used as the input variable for hydrodynamic and water quality models to predict the physical and chemical impacts such as a change in water depth, velocity and other variables that are driven by flow regulations [25,47,112,113]. In some cases, outputs from water quality or hydrodynamic models have been used as the input variables to predict the impact of dams on habitat suitability.…”
Section: Model Processes and Outputsmentioning
confidence: 99%
See 3 more Smart Citations
“…Flow is used as the input variable for hydrodynamic and water quality models to predict the physical and chemical impacts such as a change in water depth, velocity and other variables that are driven by flow regulations [25,47,112,113]. In some cases, outputs from water quality or hydrodynamic models have been used as the input variables to predict the impact of dams on habitat suitability.…”
Section: Model Processes and Outputsmentioning
confidence: 99%
“…Boavida et al [47] have illustrated that hydropeaking impact is strongly dependent on river morphology in fish habitat simulations. Furthermore, Li et al [113] suggested that the variation of hydrologic frequency, as well as the maximum and minimum amount of water release from dams due to hydropeaking, should be taken into account in model development. In many cases, there will be an overlapping effect of general river regulation and hydropeaking impacts; thus, stressors are difficult to disentangle [47].…”
Section: Weaknessesmentioning
confidence: 99%
See 2 more Smart Citations
“…The operation of the JP cascaded reservoirs would alter the natural hydrological regime in the Dahewan Reach substantially, and thus, impose severe impacts on the river ecosystem, especially on the fish habitat (Richter et al, 1997;Li et al, 2011). To protect the river ecosystem, conventional operations need to be adapted to account for ecological flow requirements (Jager and Rose, 2003;Renöfält et al, 2010).…”
Section: Introductionmentioning
confidence: 99%